Advances in knowledge-based dynamic capabilities: A systematic review of foundations and determinants in recent literature - Shimelis Tamirat; Chalchissa Amentie (Cogent Business & Management, 2023)
In contemporary dynamic and turbulent competitive business landscape, knowledge-based competition became a new normal. So far, studies gave little attention to an integration of knowledge and dynamic capabilities for business strategies, however. Therefore, this study was initiated to see recent literature developments in knowledge-based dynamic capabilities (KBDCs) as juxtaposition of both themes to identify foundational sources, factors impacting, and consequences by conducting a systematic review. The review considered 72 empirical papers published from 1 January 2015 to 19 July 2022. The findings indicated that tacit knowledge resource, knowledge management, managerial features (team composition, technological insight, and tenure), intellectual/human capital, organizational design/structure, financial resources, social capital, technology ownership and usage, existing operational and dynamic capabilities, and firm location are the foundations of KBDCs. Contextual factors affecting KBDCs at corporate interior are namely firm size, type, realized absorptive capacity, and experiential and organizational knowledge. Those external factors are new technologies, global competition, market dynamism, local business ecosystem, public innovation intermediaries, economic circumstances, and regulatory factors. Businesses used KBDCs' gained sustainable competitive advantage, improvement in resource base, and proficient in firm's business performance. Theoretical contributions, implications to practitioners, and future lines of research were discussed.
Keywords: 650; contexts; dynamic capabilities; foundations; KBDCs; knowledge management; systematic review